Ground reaction forces in distance running - Cavanagh, P. R.; Lafortune, M. A. (Journal of Biomechanics, 1980)
Ground reaction forces and center of pressure (C of P) patterns were studied in 17 subjects running at 4.5 ms-1. The subjects were classified as rearfoot or midfoot strikers according to the location of the C of P at the time of first contact between foot and ground. The C of P path in the rearfoot group showed a continuous anterior movement during support while the C of P in most of the midfoot group migrated posteriorly during the first 20 ms of the support phase. Variability in both groups was most marked during early support. The mean peak to peak force components were 3 BW, 1 BW and 0.3 BW in the vertical, anteroposterior and mediolateral directions respectively. Consistent differences between groups were noted in all three components, but individual differences within a given group were also considerable. The C of P patterns are presented in conjunction with ground reaction force data, and the implications of the results in the areas of running mechanics, shoe design and sports injury are discussed.